Pengaruh Kurs dan Inflasi Terhadap Harga Saham Perusahaan IDX-MES BUMN 17 - Nafsa Qolbina Istigfari; Astri Astri; Syahla Nur Fikriyyah; Sintia Anggraeni; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study aims to analyze the effect of exchange rates and inflation on the stock prices of companies listed in the IDX-MES BUMN 17 index during the 2020–2024 period. Exchange rate fluctuations and inflation rates are macroeconomic indicators that frequently influence capital market movements, making it important to examine how these variables impact the stock prices of companies that play a strategic role in the national economy. This study uses secondary data in the form of the rupiah exchange rate set by Bank Indonesia. The exchange rate indicator is the rupiah exchange rate against the US dollar (US$). The annual inflation rate was obtained from the Central Statistics Agency (BPS) and the year-end stock prices of each company (closing price) included in the study sample. This research is quantitative. The analytical method used is multiple linear regression using the e-Views software program. The results show that the exchange rate has a significant effect on stock prices. Meanwhile, inflation has no effect on stock prices.